1998
DOI: 10.1038/sj.leu.2400900
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Gaucher histiocytes identified up to 1 year after transplantation for CML are BCR/ABL-positive

Abstract: The results of polymerase chain reaction (PCR) analysis after transplantation for chronic myelogenous leukemia (CML) are difficult to interpret clinically. Positive findings for BCR/ABL can be seen not only in patients who go on to relapse but also in patients who, after years of follow-up, remain in complete remission. The cause for the lack of concordance between PCR findings and relapse is not clear. We identified two patients with CML who had rare pseudo-Gaucher cells in their bone marrow aspirate specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 5 publications
0
4
2
Order By: Relevance
“…For this reason, PGCs retrieved after BMT were generated from the engrafted monocyte compartment of the donor, judging by their progeny. In contrast to an anecdotal report on two patients [3], in our series we found that postgraft recurrence of PGCs did not indicate CML or a leukaemic relapse, since cytogenetic and molecular-biological data failed to disclose a clonally transformed cell population. Considering the presence of PGCs in the pretreatment bone marrow in CML, the temporal reappearance of these specific cells in a significant number of patients immediately after BMT warrants explanation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…For this reason, PGCs retrieved after BMT were generated from the engrafted monocyte compartment of the donor, judging by their progeny. In contrast to an anecdotal report on two patients [3], in our series we found that postgraft recurrence of PGCs did not indicate CML or a leukaemic relapse, since cytogenetic and molecular-biological data failed to disclose a clonally transformed cell population. Considering the presence of PGCs in the pretreatment bone marrow in CML, the temporal reappearance of these specific cells in a significant number of patients immediately after BMT warrants explanation.…”
Section: Discussioncontrasting
confidence: 99%
“…Although a wealth of data has accumulated in recent decades on the occurrence of PCGs in CML [2,3,7,10,15,18,20,31,32,34], controversy and discussion still persist about their incidence, which has been reported to range between 20% and 70% [7]. Moreover, PCGs are not only observed in CML, but occasionally also in acute myeloid leukaemia (AML) and various reactive and congenital conditions [15], including thalassaemia [40] and dyserythropoietic anaemia type II [36].…”
Section: Discussionmentioning
confidence: 99%
“…A single study has previously shown that PGC found in CML may carry BCR-ABL1 fusion [1]. In contrast, we were unable to determine their clonal origin in our case.…”
contrasting
confidence: 77%
“…It has been postulated that this may reflect a persistent CML stem cell population that expresses high levels of BCR-ABL that allow it to circumvent the effects of imatinib inhibition. A less distressing possibility is that the transcript resides in a differentiated, nonproliferating cell compartment such as pseudo-Gaucher histiocytes [76]; however, a persistent CML stem cell appears more likely, as most patients even in CCR relapse following cessation of imatinib therapy. Nevertheless, the durability of MMR in most patients indicates that imatinib can keep this small residual CML population in a quiescent state with low likelihood of secondary resistance development and very low incidence of progression to advanced phase disease.…”
Section: Monitoring Algorithms To Detect Therapy Resistancementioning
confidence: 99%